Design, synthesis, biological evaluation and molecular dynamics studies of 4-thiazolinone derivatives as protein tyrosine phosphatase 1B (PTP1B) inhibitors. Issue 13 (1st September 2020) - Liu, Wen-Shan; Wang, Rui-Rui; Yue, Hai; Zheng, Zhi-Hui; Lu, Xin-Hua; Wang, Shu-Qing; Dong, Wei-Li; Wang, Run-Ling
Abstract: Protein tyrosine phosphatase 1B (PTP1B) is a key negative regulator of insulin signaling pathway, and more and more studies have shown that it is a potential target for the treatment of type 2 diabetes mellitus (T2DM). In this study, 17 new 4-thiazolinone derivatives were designed and synthesized as novel PTP1B inhibitors, and ADMET prediction confirmed that these compounds were to be drug-like. In vitro enzyme activity experiments were performed on these compounds, and it was found that a plurality of compounds had good inhibitory activity and high selectivity against PTP1B protein. Among them, compound 7p exhibited the best inhibitory activity with an IC50 of 0.92 μM. The binding mode of compound 7p and PTP1B protein was explored, revealing the reason for its high efficiency. In addition, molecular dynamics simulations for the PTP1B WT and PTP1B comp#7p systems revealed the effects of compound 7p on PTP1B protein at the molecular level. In summary, the study reported for the first time that 4-thiazolinone derivatives as a novel PTP1B inhibitor had good inhibitory activity and selectivity for the treatment of T2DM, providing more options for the development of PTP1B inhibitors. Abbreviations: BBB blood-brain barrier CDC25B cell division cycle 25 homolog B CYP2D6 Cytochrome P450 2D6 binding DCCM dynamic cross-correlation map DS Discovery Studio H bond hydrogen bond HIA human intestinal absorption LAR leukocyte antigen-related phosphatase MD molecular dynamics MEG-2 maternal-effect germ-cell defective 2 MM-PBSA molecular mechanics Poisson Boltzmann surface area) PCA principal component analysis PDB Protein Data Bank pNPP p–nitrophenyl phosphate PPB plasma protein binding PTP1B protein tyrosine phosphotase 1B RMSD root mean square deviation RMSF root mean square fluctuation SHP-1 src homologous phosphatase-1 SHP-2 src homologous phosphatase-2 SPC single-point charge TCPTP T cell protein tyrosine phosphatase T2DM Type 2 diabetes mellitus VDW van der Waals Communicated by Ramaswamy H. Sarma